Pulsed Temperature Operation of SnO2-Based Gas Sensors - Larissa Egger; Lisbeth Reiner; Alessandro Togni; Christian Mitterer; Anton Köck (Proceedings)
We herein demonstrate the pulsed-mode temperature operation of chemical sensor devices based on thin SnO2 films, which were synthesized by magnetron sputtering. The gas-sensitive films were integrated on SiN-based micro-hotplate (µhp) chips, which enable operation temperatures up to 500 °C. We compared the gas sensor performance in constant temperature mode with pulsed temperature mode operation towards the test gases carbon monoxide and toluene. In contrast to constant temperature, the pulsed temperature mode operation reveals additional information about the type of test gas.